Expression Analysis of the Caspase10 from Olive Flounder (Paralichthys olivaceus) against Viral Hemorrhagic Septicemia Virus (VHSV) Challenge - Kim, Kyung-Hee (Dev Reprod, 2020)
The caspase10 encodes an initiating caspase that plays an important role in the maintaining the cellular homeostasis by regulating the steps involved in the immune response and cell death. We investigated the expression of caspase10 during the different developmental stages and in olive flounder tissues. Caspase10 increased in the late stage of the formation of immune tissue, and high expression was observed in the gills, kidney, skin, and spleen. The current study analyzed the expressional changes of caspase10 in olive flounder infected with viral hemorrhagic septicemia virus (VHSV). One of the major causes of mass mortality, VHSV infection in olive flounder attributes to significant expression of caspase10 in the gills, spleen, skin, and kidneys. The results indicate a close association of caspase10 expression with the immune response to VHSV infection in olive flounder. The observations could form the basis data for exploration of other fish immune system.